Análisis presupuestario del Ministerio de Desarrollo Urbano y Vivienda en el cantón Babahoyo - Hidalgo Becerra, Bryan Renato (2021)
The present investigative work aims to analyze the budgetary record of various periods of the Ministry of Urban Development and Housing where, from some occasions, it has begun to have complications in covering its institutional expenses in some of its areas due to the budget reduction to Public Entities that has been decreed at the National Level, that is, due to the deficit of the General State Budget. Where a comparative analysis of the monetary value of the Budgets of four consecutive years will be evaluated and made, determining the resources allocated for each program of the Ministry of Urban Development and Housing, also determining the structural inconsistencies that were generated in the entity as a result of the budget reduction already named, which will be detailed in the development of this case study. Where the constructive suggestions issued should be considered by the entity to improve the inconsistencies found after its respective budget analysis, taking into account the priority expenses of the institution at the time of its analysis, where the database provided by the entity did so. with absolute discretion. Carrying out the investigative work in order to improve institutionally, seeking better efficiency and effectiveness for the collection of information from the beneficiary applicants of the “Casa para Todos” program.